Posterior chamber phakic intraocular lens for the correction of high myopic anisometropic amblyopia in adults - Jing Zhang; Jing Zhuang; Ke-Ming Yu (International Journal of Ophthalmology, 2018)
This study aims to evaluate the clinical results of posterior chamber implantable collamer lens (ICL) implantation in adults with high myopic anisometropic amblyopia. Thirteen patients aged 27.04±7.24y (range 19.2 to 42.5) were studied. ICL implantation was performed in 13 amblyopic eyes. The mean myopic anisometropia was significantly dropped from -10.70±3.02 D preoperatively to +0.09±1.67 D at 1mo postoperatively. The logMAR CDVA at 3d, 1, 3 and mean 9mo postoperatively improved by a mean of 1.69, 2.50, 3.01 and 3.00 lines and gained more than 2 lines accounted for 23.08% (3 eyes), 41.67% (5 eyes), 63.63% (7 eyes) and 55.56% (5 eyes), respectively. The contrast sensitivity of amblyopic eyes was significantly increased after surgery. Four patients partially recovered near stereopsis (400” to 100”). There was no severe complications were observed. ICL implantation alone can improve vision, contrast sensitivity, and partial restoration of binocular vision in adult patients with high myopic anisometropia.